Preparation method of material based on built-in electric field regulation and control

By introducing high-reactive quantum dot sensitizers into BixMOy materials, a larger polarization field is built, which solves the problem of slow kinetics in electrocatalytic reactions, and realizes the regulation of the built-in electric field and the improvement of the reaction activity, providing new technical directions for related fields.

CN119706943APending Publication Date: 2025-03-28DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311253291.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-26
Publication Date
2025-03-28

Smart Images

  • Figure CN119706943A_ABST
    Figure CN119706943A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a material based on built-in electric field regulation and control, and the preparation method comprises the following steps: carrying out reaction I and drying I on a mixture I containing a semiconductor substrate material, a sensitizer, a surfactant I and a solvent to obtain the material based on built-in electric field regulation and control, the structural formula of the semiconductor substrate material is BixMOy, M is selected from one of Mo, V, W and Cr, the value of x is 1 or 2, and the value of y is 4 or 6; the sensitizer is a quantum dot material. According to the preparation method disclosed by the invention, the regulation and control on a built-in electric field of the Aurivillius phase compound with the layered perovskite type structure are realized by utilizing the high activity of the quantum dots. And the piezoelectric field of the original material is adjusted. The regulation and control method provides a new way for regulating the built-in electric field of the semiconductor heterostructure; the invention provides a new thought and direction for the development of materials in the fields of photocatalysis, electrocatalysis and sensing, and has wide potential scientific value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a method for preparing a material based on built-in electric field regulation, and belongs to the field of material technology. Background Art

[0002] Various electrocatalytic devices have been developed to utilize intermittent renewable energy and achieve the goal of peaking CO2 emissions. However, electrocatalytic reactions, such as hydrogen evolution reaction / oxygen evolution reaction in overall water splitting, polysulfide conversion in lithium-sulfur batteries, lithium peroxide formation / decomposition in lithium-oxygen batteries, and nitrate reduction reaction for degrading wastewater, are affected by sluggish kinetics caused by multi-electron transfer processes. Built-in electric fields are expected to overcome the above problems due to advantages such as accelerated charge transport, optimized intermediate adsorption / desorption, improved conductivity, regulation of reaction microenvironment, and easy integration with geometric features. The formation of built-in electric fields is usually related to the charge redistribution caused by the spontaneous flow of electrons at the interface. Generally speaking, when two different materials (A and B, at least one of which is a semiconductor) are in close contact with each other, the energy band difference will induce interface polarization, resulting in a potential difference. This difference will drive directional electron transport near the interface until the Fermi levels on both sides are aligned. As a result, an electron-rich region and a positively charged counterpart appear on one side, generating a charge distribution gradient and forming a built-in electric field in the direction of material A with a low work function (defined as the minimum energy required to move electrons from the Fermi level to the vacuum level) to material B with a high work function. Obviously, the electron transfer derived from the built-in electric field F directly affects the charge density around the active center, thereby enhancing the intrinsic activity. At the same time, the coexistence of electron-rich and electron-deficient regions is conducive to increasing the reactant concentration in the local microenvironment of the multiphase interface, improving the reaction rate and overall reactivity. Therefore, the construction of a built-in electric field for multi-component materials is conducive to the rapid transport of carriers to achieve their high reactivity. Summary of the invention

[0003] This application will have the original piezoelectric field of Bi x MO y (M=Mo, V, W, Cr) is used as the initial material, and quantum dot materials with high reactivity are used as sensitizers to construct a larger polarization field inside the original material to achieve the regulation of the built-in electric field.

[0004] According to one aspect of the present application, a method for preparing a material based on built-in electric field regulation is provided, the preparation method comprising:

[0005] A mixture I containing a semiconductor substrate material, a sensitizer, a surfactant I, and a solvent is reacted I and dried I to obtain the material based on built-in electric field regulation;

[0006] The structural formula of the semiconductor substrate material is Bi x MOy ,

[0007] Wherein M is selected from one of Mo, V, W, and Cr, x is 1 or 2, and y is 4 or 6;

[0008] The sensitizer is a quantum dot material.

[0009] Optionally, the method for preparing the semiconductor substrate material comprises:

[0010] In a closed reactor, a mixture II containing a Bi precursor, an M precursor, and a surfactant II is reacted II and dried II to obtain the semiconductor substrate material;

[0011] The Bi precursor is selected from bismuth nitrate and bismuth chloride;

[0012] The M precursor is selected from at least one of a Mo precursor, a V precursor, a W precursor, and a Cr precursor.

[0013] Optionally, the Mo precursor is selected from at least one of ammonium molybdate, sodium molybdate and molybdenum chloride.

[0014] Optionally, the V precursor is selected from at least one of ammonium vanadate, sodium vanadate and vanadium chloride.

[0015] Optionally, the W precursor is selected from at least one of ammonium tungstate, sodium tungstate and tungsten chloride.

[0016] Optionally, the Cr precursor is selected from at least one of chromium nitrate and chromium chloride.

[0017] Optionally, the molar ratio of the Bi precursor to the M precursor is 1-0.5:0.5-0.1.

[0018] Optionally, the mass volume ratio of the Bi precursor to the surfactant I is 1-0.5:1-0.1.

[0019] Optionally, the surfactant I and the surfactant II are independently selected from at least one of hexadecyltrimethylammonium bromide, sodium dodecyl sulfonate, and sodium dodecylbenzene sulfonate.

[0020] Optionally, the quantum dot material includes bismuth nitrate pentahydrate, Bi2Sn2O7, and Bi2O3.

[0021] Optionally, the molar ratio of the semiconductor base material to the sensitizer is 1-0.5:0.3-0.15.

[0022] Optionally, the mass ratio of the semiconductor base material to the surfactant is 1-0.5:0.1-0.05.

[0023] Optionally, the solvent is selected from at least one of nitric acid, hydrochloric acid and acetic acid.

[0024] Optionally, the mass volume ratio of the semiconductor base material to the solvent is 1 to 100 g / mL.

[0025] Optionally, the temperature of the reaction I is 120-140° C., and the time of the reaction I is 16-24 h.

[0026] Optionally, the temperature of the drying I is 40 to 70° C., and the time of the drying I is 12 to 24 hours.

[0027] Optionally, the temperature of reaction II is 170-190° C., and the time of reaction II is 16-24 h.

[0028] Optionally, the temperature of the drying II is 40 to 70° C., and the time of the drying II is 2 to 24 hours.

[0029] According to another aspect of the present application, a material based on built-in electric field regulation prepared by the above-mentioned preparation method is provided, and the material based on built-in electric field regulation is Bi2WO6-Bi2Sn2O7 or BiVO4-Bi2Sn2O7 or Bi2MoO6-Bi2Sn2O7.

[0030] As a specific implementation, the present application is implemented through the following technical solutions:

[0031] A material preparation method based on built-in electric field regulation, wherein the original substrate of the material is Bi with an original piezoelectric field x MO y (M=Mo, V, W, Cr), the built-in electric field is regulated by using highly reactive quantum dots.

[0032] B i2 Taking WO6 as an example, its preparation steps are:

[0033] (1) First, Bi2WO6 nanosheets are synthesized, and the preparation method is as follows:

[0034] In a typical synthesis process, 2mmol Bi(NO3)3·5H2O, 1mmol Na2WO4·2H2O and 0.05g CTAB were dispersed in a mixture of 30ml deionized water and stirred at room temperature for 10h. The resulting suspension was then transferred to a 50ml polytetrafluoroethylene-lined stainless steel autoclave and hydrothermally heated at 120℃ in an electrically heated oven for 24h. The powder was then collected by centrifugation, washed alternately with distilled ethanol and water several times, and then dried at 70℃ for 10h.

[0035] (2) Preparation of Bi2WO6-Bi2Sn2O7 quantum dots

[0036] A certain amount of Bi2WO6 nanosheets and a certain amount of Bi(NO3)3·5H2O were added to 15mL2mol·L -1 A certain amount of Na2SnO3 was dissolved in 15 mL of deionized water, followed by a certain amount of hexadecyltrimethylammonium bromide (CTAB), which was recorded as solution B. The two solutions were mixed and stirred for 30 min, and 1 mol·L - 1 NaOH was used to adjust the pH to 12. The mixed solution was poured into a reactor and kept at 180°C for 24 hours. After cooling to room temperature, the product was washed with water and ethanol, centrifuged and dried.

[0037] The beneficial effects of this application include:

[0038] This application uses the high activity of quantum dots to achieve the regulation of the built-in electric field of layered perovskite-type Aurivillius phase compounds and the regulation of the piezoelectric field of the original material. This regulation strategy provides a new way to regulate the built-in electric field of semiconductor heterostructures. It provides a new idea and direction for the development of materials in the fields of photocatalysis, electrocatalysis and sensing, and has broad potential scientific value. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is the SEM image of Bi2WO6-Bi2Sn2O7 prepared in Example 1 of the present application, with a scale of 100 nm. DETAILED DESCRIPTION

[0040] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0041] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0042] Example 1 Preparation of Bi2WO6-Bi2Sn2O7 Quantum Dots

[0043] (1) First, Bi2WO6 nanosheets are synthesized as follows:

[0044] 2mmol Bi(NO3)3·5H2O, 1mmol Na2WO4·2H2O and 0.05g CTAB were dispersed in a mixture of 30ml deionized water and stirred at room temperature for 10h. The resulting suspension was then transferred to a 50ml polytetrafluoroethylene-lined stainless steel autoclave and hydrothermally heated at 120℃ in an electric heating oven for 24h. The powder was then collected by centrifugation, washed alternately with distilled ethanol and water several times, and then dried at 70℃ for 10h; Bi2WO6 nanosheets were obtained.

[0045] (2) Preparation of Bi2WO6-Bi2Sn2O7 quantum dots

[0046] 0.5 g Bi2WO6 nanosheets and 0.5 g Bi(NO3)3·5H2O were added to 15 mL 2 mol·L -1 1.0 g Na2SnO3 was dissolved in 15 mL deionized water, followed by 0.25 g hexadecyltrimethylammonium bromide (CTAB), which was recorded as solution B. The two solutions were mixed and stirred for 30 min, with 1 mol·L -1 Adjust the pH to 12 with NaOH. Pour the mixed solution into a reactor and keep it at 180°C for 24 hours. After cooling to room temperature, wash the product with water and ethanol, centrifuge and dry at 60°C for 24 hours to obtain Bi2WO6-Bi2Sn2O7 quantum dots. Figure 1 As shown, from Figure 1 It can be seen that Bi2Sn2O7 quantum dots are evenly dispersed on Bi2WO6 nanosheets.

[0047] Example 2 Preparation of Bi2MoO6-Bi2Sn2O7 quantum dots

[0048] (1) First, Bi2MoO6 nanosheets are synthesized as follows:

[0049] 2mmol Bi(NO3)3·5H2O, 1mmol Na2MoO4 and 0.05g CTAB were dispersed in a mixture of 30ml deionized water and stirred at room temperature for 10h. The resulting suspension was then transferred to a 50ml polytetrafluoroethylene-lined stainless steel autoclave and hydrothermally heated at 140℃ in an electric heating oven for 24h. The powder was then collected by centrifugation, washed alternately with distilled ethanol and water several times, and then dried at 70℃ for 14h; Bi2MoO6 nanosheets were obtained.

[0050] (2) Preparation of Bi2MoO6-Bi2Sn2O7 quantum dots

[0051] 0.5 g Bi2MoO6 nanosheets and 0.5 g Bi(NO3)3·5H2O were added to 15 mL 2 mol·L -1 1.0 g Na2SnO3 was dissolved in 15 mL deionized water, followed by 0.25 g hexadecyltrimethylammonium bromide (CTAB), which was recorded as solution B. The two solutions were mixed and stirred for 30 min, with 1 mol·L -1 NaOH was used to adjust the pH to 12. The mixed solution was poured into a reactor and kept at 180°C for 24 hours. After cooling to room temperature, the product was washed with water and ethanol, centrifuged, and dried at 60°C for 24 hours to obtain Bi2MoO6-Bi2Sn2O7 quantum dots.

[0052] Example 3 Preparation of BiVO4-Bi2Sn2O7 quantum dots

[0053] (1) First, BiVO4 nanosheets are synthesized as follows:

[0054] 2mmol Bi(NO3)3·5H2O, 1mmol Na3VO4 and 0.05g CTAB were dispersed in a mixture of 30ml deionized water and stirred at room temperature for 10h. The resulting suspension was then transferred to a 50ml polytetrafluoroethylene-lined stainless steel autoclave and hydrothermally heated at 140℃ in an electric heating oven for 16h. The powder was then collected by centrifugation, washed alternately with distilled ethanol and water several times, and then dried at 70℃ for 14h; BiVO4 nanosheets were obtained.

[0055] (2) Preparation of BiVO4-Bi2Sn2O7 quantum dots

[0056] 0.5 g BiVO4 nanosheets and 0.5 g Bi(NO3)3·5H2O were added to 15 mL 2 mol·L -1 1.0 g Na2SnO3 was dissolved in 15 mL deionized water, followed by 0.25 g hexadecyltrimethylammonium bromide (CTAB), which was recorded as solution B. The two solutions were mixed and stirred for 30 min, with 1 mol·L -1 NaOH was used to adjust the pH to 12. The mixed solution was poured into a reactor and kept at 180°C for 24 hours. After cooling to room temperature, the product was washed with water and ethanol, centrifuged, and dried at 60°C for 24 hours to obtain BiVO4-Bi2Sn2O7 quantum dots.

[0057] Example 4 Preparation of Bi2CrO6-Bi2Sn2O7 Quantum Dots

[0058] (1) First, Bi2CrO6 nanosheets are synthesized as follows:

[0059] 2mmol Bi(NO3)3·5H2O, 1mmol chromium nitrate and 0.05g CTAB were dispersed in a mixture of 30ml deionized water and stirred at room temperature for 10h. The resulting suspension was then transferred to a 50ml polytetrafluoroethylene-lined stainless steel autoclave and hydrothermally heated at 140℃ in an electric heating oven for 16h. The powder was then collected by centrifugation, washed alternately with distilled ethanol and water several times, and then dried at 70℃ for 14h; Bi2CrO6 nanosheets were obtained.

[0060] (2) Preparation of Bi2CrO6-Bi2Sn2O7 quantum dots

[0061] 0.5 g Bi2CrO6 nanosheets and 0.5 g Bi(NO3)3·5H2O were added to 15 mL 2 mol·L -1 1.0 g Na2SnO3 was dissolved in 15 mL deionized water, followed by 0.25 g hexadecyltrimethylammonium bromide (CTAB), which was recorded as solution B. The two solutions were mixed and stirred for 30 min, with 1 mol·L -1 NaOH was used to adjust the pH to 12. The mixed solution was poured into a reactor and kept at 180°C for 24 hours. After cooling to room temperature, the product was washed with water and ethanol, centrifuged, and dried at 60°C for 24 hours to obtain Bi2CrO6-Bi2Sn2O7 quantum dots.

[0062] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method for preparing a material based on built-in electric field regulation, characterized in that: The preparation method comprises: A mixture I containing a semiconductor substrate material, a sensitizer, a surfactant I, and a solvent is reacted I and dried I to obtain the material based on built-in electric field regulation; The structural formula of the semiconductor substrate material is Bi x MO y , Wherein M is selected from one of Mo, V, W, and Cr, x is 1 or 2, and y is 4 or 6; The sensitizer is a quantum dot material.

2. The preparation method according to claim 1, characterized in that: The method for preparing the semiconductor substrate material comprises: In a closed reactor, a mixture II containing a Bi precursor, an M precursor, and a surfactant II is reacted II and dried II to obtain the semiconductor substrate material; The Bi precursor is selected from bismuth nitrate and bismuth chloride; The M precursor is selected from at least one of a Mo precursor, a V precursor, a W precursor, and a Cr precursor.

3. The preparation method according to claim 2, characterized in that: The Mo precursor is selected from at least one of ammonium molybdate, sodium molybdate and molybdenum chloride; Preferably, the V precursor is selected from at least one of ammonium vanadate, sodium vanadate and vanadium chloride; Preferably, the W precursor is selected from at least one of ammonium tungstate, sodium tungstate and tungsten chloride; Preferably, the Cr precursor is selected from at least one of chromium nitrate and chromium chloride; Preferably, the molar ratio of the Bi precursor to the M precursor is 1-0.5:0.5-0.1; Preferably, the mass volume ratio of the Bi precursor to the surfactant I is 1-0.5:1-0.

1.

4. The preparation method according to claim 1 or 2, characterized in that: The surfactant I and the surfactant II are independently selected from at least one of cetyltrimethylammonium bromide, sodium dodecyl sulfonate, and sodium dodecylbenzene sulfonate.

5. The preparation method according to claim 1, characterized in that: The quantum dot materials include Bi2Sn2O7 and Bi2O3.

6. The preparation method according to claim 1, characterized in that: The molar ratio of the semiconductor base material to the sensitizer is 1-0.5:0.3-0.15; Preferably, the mass ratio of the semiconductor base material to the surfactant is 1-0.5:0.1-0.

05.

7. The preparation method according to claim 1, characterized in that: The solvent is selected from at least one of nitric acid, hydrochloric acid and acetic acid; Preferably, the mass volume ratio of the semiconductor base material to the solvent is 100 to 50 g / mL.

8. The preparation method according to claim 1, characterized in that: The temperature of the reaction I is 120-140° C., and the time of the reaction I is 16-24 hours; Preferably, the temperature of the drying I is 40 to 70° C., and the time of the drying I is 12 to 24 hours.

9. The preparation method according to claim 2, characterized in that: The temperature of the reaction II is 170-190°C, and the time of the reaction II is 16-24h; Preferably, the temperature of the drying II is 40 to 70° C., and the time of the drying II is 12 to 24 hours.

10. The material based on built-in electric field regulation prepared by the preparation method according to any one of claims 1 to 9, characterized in that: The material based on built-in electric field regulation is Bi2WO6-Bi2Sn2O7 or Bi2MoO6-Bi2Sn2O7 or BiVO4-Bi2Sn2O7 or Bi2CrO6-Bi2Sn2O7.